2013
DOI: 10.1155/2013/254250
|View full text |Cite
|
Sign up to set email alerts
|

Root Anatomy and Root Canal Configuration of Human Permanent Mandibular Premolars: A Systematic Review

Abstract: Introduction. Mandibular premolars have been reported with complex anatomical aberrations, making them one of the most difficult teeth to manage endodontically. Methodology. An exhaustive search was undertaken to identify associated anatomic studies of mandibular premolars through MEDLINE/PubMed database using keywords, and a systematic review of the relevant articles was performed. Chi-square test with Yates correction was performed to assess the statistical significance of any anatomic variations between eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
77
2
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(109 citation statements)
references
References 77 publications
28
77
2
2
Order By: Relevance
“…Zillich and Dowson reported 11.7% and 0.4% occurrence of two canals and three canals in mandibular premolars respectively [4]. Cleghorn et al in a literature review, reported that the incidence of an additional root (0.4%), an additional canal (9.9%), and an additional apical exit (8.2%) in the mandibular second bicuspids is lower than that of the mandibular first bicuspids (2.0%, 24.2%, and 21.1%, respectively) [5].Overall, an accessory root was present only in about 0.0-4.4% (average 0.61%) of teeth as reported in a systematic review by Kottoor et al [6].In Indian population, this presentation of second premolars with two root canals was reported to be 13.5-20% [7].Hence, the endodontic management of mandibular second premolars with variable canal configuration can be diagnostically and technically challenging. In light of these observations, this article highlights a case report of successful endodontic management of a mandibular second premolar with variable canal pattern.…”
Section: *Correspondencementioning
confidence: 77%
“…Zillich and Dowson reported 11.7% and 0.4% occurrence of two canals and three canals in mandibular premolars respectively [4]. Cleghorn et al in a literature review, reported that the incidence of an additional root (0.4%), an additional canal (9.9%), and an additional apical exit (8.2%) in the mandibular second bicuspids is lower than that of the mandibular first bicuspids (2.0%, 24.2%, and 21.1%, respectively) [5].Overall, an accessory root was present only in about 0.0-4.4% (average 0.61%) of teeth as reported in a systematic review by Kottoor et al [6].In Indian population, this presentation of second premolars with two root canals was reported to be 13.5-20% [7].Hence, the endodontic management of mandibular second premolars with variable canal configuration can be diagnostically and technically challenging. In light of these observations, this article highlights a case report of successful endodontic management of a mandibular second premolar with variable canal pattern.…”
Section: *Correspondencementioning
confidence: 77%
“…Knowledge of dental anatomy is essential for learning clinical operative dentistry procedures (Kottor, Albuquerque, Velmurugan, & Kuruvilla, 2013). Therefore, teaching clinical procedures substantiated by data on human dental anatomy reinforces its clinical relevance and the need for training (Hagen, Cooke, & Wright, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro measurements of RCL in a large sample (n = 70) of extracted primary teeth obtained by the standard direct tactile method might contribute to the knowledge of the anatomy of such teeth and to clinical endodontic procedures (Kottor, Albuquerque, Velmurugan, & Kuruvilla, 2013), since few studies had been published (Mello-Moura et al, 2010;Subramaniam, Konde, & Mandanna, 2005;Oznurhan et al, 2014;Wankhade, Kumar, Singh, & Chandra, 2013), most with smaller samples (Mello-Moura et al, 2010;Subramaniam, Konde, & Mandanna, 2005;Oznurhan et al, 2014). In addition, teaching and exploring the dental anatomy in integration with clinical procedures emphasizes the clinical relevance of basic sciences (Hagen, Cooke, & Wright, 2017) while increases the clinical competence of dental students to perform endodontic procedures.…”
Section: Introductionmentioning
confidence: 99%
“…of canals Comments References 1st premolar 1 (73%-89%) One canal may separate into two; The C-shaped canal occurs in 10-14% of cases 2 or more canals in women 2 (25%-27%) Baisden et al 1992;Sikri and Sikri, 1994;Carrotte, 2004;Jafarzadeh, 2007;Kottoor et al 2013;Fernandes et al 2014 2nd premolar 1 (62%-85%) 1 canal may separate into two; C-shaped canal occurs Multiple canals in men Vertucci, 1984;Carrotte, 2004 2 (5%-15%) Carrotte, 2004;Kottoor et al 2013;Fernandes et al 2014 1st molar 3 (67%) 2 canals in the mesial root and 1 canal in the distal root occurs; C-shaped canal occurs; An additional canal occurs in distal root Vertucci, 1984Vertucci, , 2005Carrotte, 2004;Cleghorn et al 2006;Jafarzadeh and Wu, 2007;Cleghorn et al 2012 4 (25%-29% 1 ,…”
Section: Toothmentioning
confidence: 99%
“…The precise etiology of accessory canal formation remains elusive. Among the factors believed to contribute to canal configura-tions are sex (Ahmed et al 2007;Kottoor et al 2013), geography (Sert and Bayirli 2004;Awawdeh et al 2008;Al-Qudah and Awawdeh 2009) and ethnicity (Kottoor et al 2013;Amardeep et al 2014).…”
Section: Introductionmentioning
confidence: 99%